Thermal treatment and ammoniacal leaching for the recovery of valuable metals from spent lithium-ion batteries. (May 2018) - Chen, Yongming; Liu, Nannan; Hu, Fang; Ye, Longgang; Xi, Yan; Yang, Shenghai
Highlights: Phase transformations during the thermal treatment were determined. Selective/complete leaching of valuable metals were achieved by ammoniacal reagents. The corresponding relationship between the leaching efficiencies and phase evolution of object element was investigated. A reasonable strategy for utilizing the spent LIBs was briefly proposed. Abstract: The recycling of spent commercial lithium-ion batteries (LIBs) generates numerous environmental and economic benefits. In this research, a thermal treatment-ammoniacal leaching process is proposed to recover valuable metals from cathode active powder. Based on the thermal behavior by TG-DSC analysis, the cathode active powder is calcined at 300 °C and 550 °C in air atmosphere, and the crystalline phase characterization indicates that a new phase of Co3 O4 appears in the cathode active powder calcined at 550 °C, which signifies that the layer structure of LiCoO2 collapses. The valence of manganese increases to form Li4 Mn5 O12 in spinel structure of LiMn2 O4 . Using calcined cathode powder as feed material, ammoniacal leaching is carried out in (NH4 )2 SO4 -(NH4 )2 SO3 solution. Under the optimum conditions, Ni, Co, Mn and Li can be completely leached out with efficiencies of 98%, 81%, 92% and 98%, respectively. However, with the increase of ammonia concentration, the leaching efficiency of Mn decreases dramatically to 4% due to the formation of double salts. It is found that Co and Mn can be precipitated into residues in the form of (NH4 )2 Co(SO4 )2 ·H2 O, (NH4 )2 Mn(SO3 )2 ·H2 O and (NH4 )2 Mn(SO4 )2 ·6H2 O under different leaching parameters. Based on the corresponding relationship between the leaching efficiency and phase evolution of object element, selective leaching can be achieved by controlling the formation of double salts.